Analysis Of The Role Of Sipakatau, Sipakalebbi, Sipakainge' As Cultural Values For Juvenile Crime Cases In Panakukkang Sub-District, Makassar City - Muh. Fauzan Anwar; Devi Triyana; Ayu Purnama Sari; Novayagori Tarmizi; Ayrin Eka Putri A (Publikasi Indonesia, 2023)
This research aims to 1. Find out how the community understands the cultural values of Sipakatau, Sipakalebbi, and Sipakainge' in Panakkukang District, Makassar City. 2. Analyze the role of Sipakatau, Sipakalebbi, and Sigunakannge' in cases of juvenile crime in Panakkukang District, Makassar City. This research uses a qualitative descriptive approach to reveal the real situation in implementing the cultural values of Sipakatau, Sipakalebbi, and Sipakainge' by the people of Panakkukang District, Makassar City. The subjects of this research were informants who were taken by purposive sampling from the community, cultural experts, and government officials in Panakkukang District, Makassar City. Data and information collection techniques were carried out through interviews (in-depth interviews), participatory observation, as well as document studies and literature studies. The results of the study were then analyzed using the interactive model of Miles, Huberman, and Saldana, namely data condensation, data presentation, and conclusion. The results of this research show that the cultural values of Sipakatau, Sipakalebbi, and Sipakainge' as a way of life for the Makassar Bugis community have a very large role in preventing intolerant behavior in the Makassar Bugis community